Maximum temperature beneath the ceiling in tunnel fires with combination of ceiling mechanical smoke extraction and longitudinal ventilation. (September 2017) - Tang, F.; Mei, F.Z.; Wang, Q.; He, Z.; Fan, C.G.; Tao, C.F.
Highlights: Maximum temperature was studied in tunnel fires with ceiling point extraction. The maximum temperature decreases linearly with the ceiling extraction velocity. Proposed correlation was to be applicable with and without ceiling extraction. Abstract: This paper experimentally investigated the maximum temperature of smoke flow under the ceiling with the combined effect of ceiling mechanical exhaust system and longitudinal ventilation. Experiments were carried out in a tunnel model with dimensions of 66 m × 1.5 m × 1.3 m (length × width × height). The longitudinal ventilation wind speed was set by 0–1.2 m/s, while the ceiling extraction velocity was 0–2.2 m/s with the fire heat release rate of 30–50 kW. Smoke temperature beneath the tunnel ceiling was measured by K-type thermocouples. The experimental results showed that the ceiling mechanical exhaust system will affect the smoke control, due to the interactions between induced ambient air flow near the ceiling mechanical exhaust vent and longitudinal ventilation. The actual longitudinal air flow velocity would decrease with the ceiling extraction velocity increased, when the fire source was placed downstream of the ceiling extraction vent. The maximum smoke temperature beneath the tunnel ceiling decreased linearly with the ceiling extraction velocity without longitudinal ventilation. A modified model was put forward to predict the maximum temperature of smoke flow beneath the ceiling with combined effect of ceiling single point extraction and longitudinal ventilation in tunnel fires.